Atrazine-Based Molecularly Imprinted Polymer As Electrochemical Sensor For Pesticide Detection - Lah, Nuur Fahanis Che (2019)
The wide-ranging use of pesticides causes concern for their effect on human as well as animal life, which is in direct and indirect contact with hazardous compounds through pesticide build-up in food and drinking water. Therefore, this study aimed of the outmost importance to develop methods and techniques for atrazine detection in aqueous solutions. Highly crosslinked polymers have been prepared by precipitation polymerization using high monomer loadings (≥ 25 v/v %) which generally lead to bulk monolith. The formulation of the polymer was modified by varying the Methacrylic Acid (MAA) as the monomer and Ethylene Glycol Dimethacrylate (EDGMA) as the crosslinker ratio together with several types of porogenic solvent. It was observed that the formulation of 1:15:40 (Atr:EDGMA:MAA) with 5% of Dimethyl Sulfoxide (DMSO) and 95% of toluene as the porogen mixture improves the efficiency of the imprinted polymer compared to the formulation in 100% of toluene. The binding capacity increase for almost 18% from the original formulation. Two distinct morphologies were observed. Monodispersed microspheres were obtained using toluene whereas segmented irregular particles were formed with DMSO. The ratio of monomer, crosslinker and the type of solvent mixture were identified as influential parameters on the particle morphology. The adsorption equilibrium data showed that the imprinted polymer resulted in the lowers error for Jovanovic isotherm model. The adsorption kinetics of atrazine on MIPs was studied and found to fit the best with Lagergen first order kinetic model. The optimum formulation of imprinted polymer was assembled with graphite felt electrode as the transduction for electrochemical analysis. Cyclic voltammetry (CV) and electrochemical impedance spectrum (EIS) were used to characterize the sensor and investigate the electrochemical response of the sensor. The heterogeneous electron transfer constant, k0 that was calculated from CV indicates that the constant fall between the quasi reversible system with 0.0661 cm.s-1 for anodic and 0.0195 cm.s-1 for cathodic. The limit of detection (LOD) for the system was found to be at 4.99 nM. An equivalent circuit was suggested from the Nyquist plot that gives good fits with χ2 value between 0.6298 and 1.475 interpret the process of molecule diffusion from the bulk solution onto the electrode surface by quantitatively analyse each component of the sensor system. With the proposed methodology, electrochemical atrazine-based molecular imprinted polymers (MIPs) sensor have been prepared successfully in high monomer concentration with the improvement by manipulating the porogen/solvent mixture.